RETRACTED: Neuroprotective Effects of Ginsenoside-Rg1 Against Depression-Like Behaviors via Suppressing Glial Activation, Synaptic Deficits, and Neuronal Apoptosis in Rats - Fan, Cuiqin; Song, Qiqi; Wang, Peng; Li, Ye; Yang, Mu; Yu, Shu Yan (Frontiers in Immunology, 2018)
Depression is considered a neuropsychiatric disease associated with various neuronal changes within specific brain regions. We previously reported that ginsenoside-Rg1, a potential neuroprotective agent extracted from ginseng, significantly alleviated depressive-like disorders induced by chronic stress in rats. However, the mechanisms by which ginsenoside-Rg1 exerts its neuroprotective effects in depression remain largely uncharacterized. In the present study we confirm that ginsenoside-Rg1 significantly prevented the antidepressant-like effects in a rat model of chronic unpredictable mild stress (CUMS) and report on some of the underlying mechanisms associated with this effect. Specifically, we found that chronic pretreatment with ginsenoside-Rg1 prior to stress exposure significantly suppressed inflammatory pathway activity via alleviating the overexpression of proinflammatory cytokines and the activation of microglia and astrocytes. These effects were accompanied with an attenuation of dendritic spine and synaptic deficits as associated with an upregulation of synaptic-related proteins in the ventral medial prefrontal cortex (vmPFC). In addition, ginsenoside-Rg1 inhibited neuronal apoptosis induced by CUMS exposure, increased Bcl-2 expression and decreased cleaved Caspase-3 and Caspase-9 expression within the vmPFC region. Taken together, these results suggest that the neuroprotective effects of ginsenoside-Rg1, which may assume the antidepressant-like effect in this animal model of depression, appears to result from amelioration of a CUMS-dependent neuronal deterioration within the vmPFC. Moreover, they also provide support for the therapeutic potential of ginsenoside-Rg1 in the treatment of stress-related mental disorders.